Bacterial conjunctivitis: microbiological profile and molecular characterization of Methicillin-Resistant Staphylococci isolated from Minia governorate, Egypt - Fatma Ahmed Abdel Aziz; Gamal Fadl Mahmoud Gad; Ahmed Mohamed Kamal El Shafei; Reham Ali Ibrahem (Novel Research in Microbiology Journal)
Ocular infections caused by bacterial sources are a global health issue that can damage the construction of the eye, and lead to disability. The goals of this study were to look at the bacterial species causing conjunctivitis, as well as their antibacterial susceptibility patterns. In addition to emphasizing on detecting the predominance of certain virulence genes of Methicillin Resistant Staphylococcus aureus (MRSA), and Methicillin Resistant coagulase negative Staphylococci (MR-CoNS), which are known to cause conjunctivitis. In this study, several swabs of bacterial conjunctivitis were sampled from patients who attended to the Ophthalmology department, Minia University and Malawi Ophthalmology hospital, Egypt. A total of 200 eye swab samples were analyzed over the entire period of the study. Results showed that about 133 eye swab samples expressed growth of about 147 pathogenic bacterial spp. The predominant isolated bacteria were Staphylococcus aureus (44.89 %), followed by Coagulase negative Staphylococci (29.9 %). On the contrary, Esherichia coli, Pseudomonas aeruginosa, Proteus sp., Streptococcus pneumonia, Klebsiella sp., and Haemophilus influenzae, were the least detected bacterial spp. Most of the bacterial isolates tested in this study exhibited high resistance to Amoxacillin-Clavulanic, Sulfamethoxazole-trimethoprim, Cefotaxime, and Cefoperazone. Using Cefoxitin, results of the phenotypic test predicted that 40.9 % of the Staphylococcal spp. were MRSA, and 23.6 % were MR-CoNS. The Polymerase chain reaction (PCR) technique was used to explore the presence of several bacterial pathogenicity genes, including MecA, PVL, icaA, icaD, and Hla in the MRSA and in MR-CoNS. Results of the PCR revealed that all MRSA and MR-CoNS had MecA, icaA, and icaD genes, whereas 28.9 % of the MRSA had PVL and Hla. However, no isolate of MR-CoNS recorded the presence of the PVL or HLa genes. This study showed that prevalence of the bacterial eye conjunctivitis has increased with MRSA dominance. All the MRSA possessed at least the icaA, and icaD virulence genes beside the MecA gene, which confirm their roles in the pathogenesis of conjunctivitis.